Posterior Fossa Arteriovenous Malformations: Experience with 14 Patients and a Systematic Review of the Literature - Corniola, Marco V.; Meling, Torstein R.; Bijlenga, Philippe; Bernava, Gianmarco; Machi, Paolo; Schaller, Karl (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Background The optimal management of posterior fossa arteriovenous malformations (pfAVMs) is a matter of debate. To advance this discussion, we present our clinical series and the results of a systematic literature review according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines.Methods Fourteen consecutive patients with pfAVMs were admitted between 2007 and 2018. Preoperative status, radiologic parameters, and outcome were assessed. A systematic literature review was performed according to the PRISMA-P guidelines.Results Ten patients presented with rupture (71%), of whom three had associated aneurysms (AAs). The treatments were microsurgery (n = 4), endovascular (n = 3), radiosurgery (n = 2), a combination of two or three treatment modalities (n = 3), or conservative (n = 2). At discharge, all four patients (100%) with unruptured pfAVMs had a good outcome (modified Rankin Scale [mRS]: 0–2). In contrast, in ruptured pfAVM cases, mRS was 0 to 2 in four patients (40%), mRS 3 to 4 in two (20%), mRS 5 in three (30%), and one patient (10%) died within 30 days after gamma knife treatment due to pancreatitis secondary to chronic alcohol abuse. At discharge, four patients (29%) had persistent preinterventional cranial nerve and/or focal neurologic deficits. The literature review identified 63 articles with 1,753 pfAVM patients. Overall, 66% of pfAVMs presented with rupture, and AAs were found in 20% of the cases, which is higher than in supratentorial AVMs (stAVMs).Conclusions Because pfAVMs are associated with higher rates of hemorrhagic presentation, higher rates of morbidity and mortality when ruptured, and have a higher incidence of AAs compared with stAVMs, early curative treatment is recommended as soon as the diagnosis is established, regardless of rupture status.
Keywords: posterior fossa; arteriovenous malformations; endovascular therapy; microsurgery; intracerebral hemorrhage; angioarchitecture